Alzheimer's in 3D culture: Challenges and perspectives. (7th August 2015) - D'Avanzo, Carla; Aronson, Jenna; Kim, Young Hye; Choi, Se Hoon; Tanzi, Rudolph E.; Kim, Doo Yeon
<x xml:space="preserve">Abstract</x> Alzheimer's disease (AD) is the most common cause of dementia, and there is currently no cure. The "β‐amyloid cascade hypothesis" of AD is the basis of current understanding of AD pathogenesis and drug discovery. However, no AD models have fully validated this hypothesis. We recently developed a human stem cell culture model of AD by cultivating genetically modified human neural stem cells in a three‐dimensional (3D) cell culture system. These cells were able to recapitulate key events of AD pathology including β‐amyloid plaques and neurofibrillary tangles. In this review, we will discuss the progress and current limitations of AD mouse models and human stem cell models as well as explore the breakthroughs of 3D cell culture systems. We will also share our perspective on the potential of dish models of neurodegenerative diseases for studying pathogenic cascades and therapeutic drug discovery.